Efficient Data Forwarding Mechanism in Backbone Networks by Employing MPLS Technology - Iltaf, Walid (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Multiprotocol Label Switching (MPLS) is a relatively new WAN technology that is attracting the networking professionals around the globe. Many ISPs have already deployed it in their network. Yet, some other ISPs are in the pipeline to deploy it. Nevertheless, it has caught the attention of professionals soon after it was developed. Instead of the IP address or MAC address, MPLS works on small labels. These labels are inserted between Data Link layer and Network layer of the OSI model. Forwarding decisions are based on these labels; instead of looking at complex routing tables. The MPLS network is configured, and tested under different conditions. A comparison is drawn between the IP and MPLS network. The obtained results show that MPLS has a lower end to end delay and less CPU utilization. Furthermore, MPLS has lesser processing delay as compared to the IP network. The performance difference is basically due to the intelligent forwarding mechanism of MPLS technology. It is also important to further investigate this topic in terms of security considerations. The labels values are not encrypted during transmission, and there is no authorization mechanism defined. It will be highly beneficial to have more sophisticated suite of security tools to encounter threats and vulnerabilities.